Mobilisation of HLA‐F on the surface of bronchial epithelial cells and platelets in asthmatic patients. (30th August 2022) - Fiouane, Sabrina; Chebbo, Mohamad; Beley, Sophie; Paganini, Julien; Picard, Christophe; D'Journo, Xavier‐Benoît; Thomas, Pascal‐Alexandre; Chiaroni, Jacques; Chanez, Pascal; Gras, Delphine; Di Cristofaro, Julie
Abstract : Uncontrolled inflammation of the airways in chronic obstructive lung diseases leads to exacerbation, accelerated lung dysfunction and respiratory insufficiency. Among these diseases, asthma affects 358 million people worldwide. Human bronchial epithelium cells (HBEC) express both anti‐inflammatory and activating molecules, and their deregulated expression contribute to immune cell recruitment and activation, especially platelets (PLT) particularly involved in lung tissue inflammation in asthma context. Previous results supported that HLA‐G dysregulation in lung tissue is associated with immune cell activation. We investigated here HLA‐F expression, reported to be mobilised on immune cell surface upon activation and displaying its highest affinity for the KIR3DS1‐activating NK receptor. We explored HLA‐F transcriptional expression in HBEC; HLA‐F total expression in PBMC and HBEC collected from healthy individuals at rest and upon chemical activation and HLA‐F membrane expression in PBMC, HBEC and PLT collected from healthy individuals at rest and upon chemical activation. We compared HLA‐F transcriptional expression in HBEC from healthy individuals and asthmatic patients and its surface expression in HBEC and PLT from healthy individuals and asthmatic patients. Our results support that HLA‐F is expressed by HBEC and PLT under healthy physiological conditions and is retained in cytoplasm, barely expressed on the surface, as previously reported in immune cells. In both cell types, HLA‐F reaches the surface in the inflammatory asthma context whereas no effect is observed at the transcriptional level. Our study suggests that HLA‐F surface expression is a ubiquitous post‐transcriptional process in activated cells. It may be of therapeutic interest in controlling lung inflammation.